Stunting and Head Circumference Growth in The First 3 Years of Life - Priyantini, Sri; Nuha, Mohamad; Purnasari, Perez; Masyhudi, AA (Jurnal Kesehatan Masyarakat, 2024)
The prevalence of stunting in Indonesia still exceeds WHO recommended standards. Stunting increases the risk of inhibition of brain growth. Head circumference is one of the parameters of brain growth. The study aimed to prove the mean head circumference growth difference between the stunted and non-stunted groups in the first 3 years of life. Another goal was to prove the relationship between zinc intake and zinc levels in toddlers on head circumference. The cohort study involved 50 subjects who were observed from birth to the age of 3 years and were born at Sultan Agung Islamic Hospital and Bangetayu Health Center Semarang City. The mean head circumference growth in the stunting group was lower than in the non-stunting group (4.1 v.s 4.6), p=0.043. The mean head circumference of stunted toddlers was smaller than that of non-stunted toddlers (44.9 vs. 47.2 ), p=0.000. There was no relationship between daily zinc intake and zinc levels of toddlers with stunting, p0.05. The growth of the head circumference of stunted toddlers was lower than in the non-stunted group, as well as the head circumference was smaller than in the non-stunted group.